Behavior of Ethidium Bromide-Hoechst 33258-DNA and Ethidium Bromide-Methylene Blue-DNA Triple Systems by means of UV Melting. (1st December 2015) - Vardevanyan, Poghos O.; Antonyan, Ara P.; Parsadanyan, Marine A.; Shahinyan, Mariam A.; Melkonyan, Gayane A.
Abstract : The study of EtBr and H33258 interaction as well as EtBr and MB interaction with DNA has been carried out. It was revealed that, at joint interaction, the effect of two ligands on the change of melting thermodynamic parameters of EtBr-DNA-H33258 or EtBr-DNA-MB complexes is not an addition of separate interaction influences. It was shown that, at joint, binding of EtBr and MB with DNA competition occurs, while in the case of EtBr and H33258, the mutual strengthening of stabilizing effect of each of them on DNA double-stranded structure mainly takes place.